Impact of nymph to adult food-switch and of adult food-stress on Nezara viridula (Hemiptera: Pentatomidae) biology - Panizzi, Antônio R.; Meneguim, Ana M.; Rossini, Maria C. (Pesquisa Agropecuaria Brasileira, 2014)
Laboratory studies of adult southern green stink bug Nezara viridula (L.) demonstrated that this species exhibited differences in performance (i.e., survivorship, longevity, reproductive parameters, and body weight changes) depending on the different food-switches from nymph to adult and on the nutritional stress imposed to adults. In general, survivorship and longevity of adults on immature soybean [Glycine max (L.) Merrill] fed - ISP - and on mature soybean seed - MSS - were greater when nymphs fed ISP, compared to adults that were fed green bean (Phaseolus vulgaris L.) fed - GBP - when nymphs. Nymphs reared on ISP, fed soybean stem + leaf (SSL) or starved when adults, showed reduced longevity. Reproductive performance of females of N. viridula fed GBP, either as nymphs or as adults, was smaller compared to females fed ISP or MSS; no females reproduced when fed SSL or starved. In most foods females fed ISP as nymphs showed greater and earlier peaks of weight gain than those fed GBP as nymphs. Daily weight gain of N. viridula, previously starved for 24 hours, was greater during the its than during the 2nd week of adult life. Total body lipid content decreased due to continuous starvation.